Development of Quizizz Application E-Module-Based Teaching Materials on Student Mathematics Learning Outcomes - Nur, Zeni Eva Hoerunisa; Raharjo, Hendri; Wahid , Sirojudin (Educational Insights, 2023)
Teaching materials have an important role for the continuation of learning so that student learning outcomes are more optimal. Teachers must create a learning media and teaching materials that of course so that students feel interested and active during learning. During a pandemic like this, online learning is certainly not effective if the use of print-based teaching materials is carried out, due to the limited communication between students and teachers. One of the teaching materials that can be sought to improve student learning outcomes is E-Module-based teaching materials with the Quizizz application. The population is all students of Class VII of SMP Negeri 2 Sumber for the 2021/2022 school year. Samples in this study. The class used is class VII G as the control class and VII I as the experimental class. The instruments used are tests and questionnaires. The results of this research are: Based on the validation results from material experts and media experts that the development of e-module-based teaching materials with the quizizz application is suitable for use as mathematics teaching materials and Students' mathematics learning outcomes increase after the provision of e-module teaching materials with the quizizzi application in the learning process.